Trente ans de didactisation du corse - Alain Di Meglio; Nicolas Sorba (Lengas)
This article is devoted to the process of didactic transposition of the Corsican language. It proposes to study the conditions for the development of school textbooks from the extension of the Deixonne Law to Corsica (1974). In addition to the precise information it provides on the quality of textbooks, their authors, the conditions for their publication, their inclusion in the various approaches to language teaching or their linguistic content, this presentation also aims to provide a context that helps to understand the systemic conditions for the recognition of a minority language.